Prevalence and predictors of potential drug–drug interactions in patients of internal medicine wards of a tertiary care hospital in India. Issue 5 (19th July 2017) - Bethi, Yugandhar; Shewade, Deepak Gopal; Dutta, Tarun Kumar; Gitanjali, Batmanabane
Abstract : Background: Drug–drug interactions are a major source of adverse drug events (ADEs). Polypharmacy, age and the number of comorbid conditions are important predictors of adverse drug interactions. ADEs account for up to 5% of hospital admissions per year and an increase in the length of hospital stay. Objective: To find the prevalence and predictors of potential drug–drug interactions (pDDIs) in patients admitted to the wards of an internal medicine department of a tertiary care hospital. Method: Patients admitted to internal medicine wards with prescriptions having more than one drug were selected. Demographic details including age, gender, number of comorbid conditions, number of drugs prescribed and the disease for which the patient was admitted were recorded in a case record form. Interactions were checked using Micromedex DrugReax software. Results: A total of 939 patients were recruited for this study based on inclusion criteria. 433 prescriptions (46%) had one or more pDDIs, with a range of 1–13 drug interactions per prescription. A total of 1395 drug interactions were found, with 866 moderate drug interactions (62%), 435 major interactions (31.1%) and 89 minor interactions (6.3%). During the study period only three contraindicated drug combinations (0.2%) were recorded. A significant association (p<0.01) was found between the number of pDDIs and predictors, age and number of drugs. Conclusion: A total of 433 prescriptions (46%) had one or more pDDIs. Older patients and those prescribed >6 drugs are at major risk for occurrence of pDDIs. Moderate severity interactions were the highest number followed by major severity interactions.